An Overview about the Historical Landmarks in the City of Old Nedroma (مجلة الواحات للبحوث والدراسات, 2025)
The ancient city of Nadroma is considered one of the well-known cities among the cities of the Islamic Maghreb in the past. It was preferred by the sultans to live in. It had a special place among the Zayani sultans, as Yahya bin Khaldoun mentioned that Sultan Othman ibn Yaghmurasen was deeply saddened by its occupation by the Marinid Sultan Abi Yahya, the brother of Sultan Yusuf. Abu Yaqoub Al-Marini, then was soon recovered by the Zayanis, leaving behind a good number of archaeological evidence, in addition to what the Turks left after them. From this stand point, we decided to present this research paper as an extensive reading of the ancient Islamic architectural monuments in the city of Nadroma and it came in the nature of  the diversity between what is religious, civil and military, similar to the Islamic cities that shared time and space with them, and we deliberately mentioned examples of each character, in order to fulfill the right of the subject, and make this research paper as an identification card for the richness of the city of the exploits of the current and subsequent generations.Keywords: Nedroma, The Great Mosque, The Qaddarin Mosque, The Sultan’s Castle, The Shrines.